Mechanical design and manufacture of a boundary layer pump - Bufalari, Lapo; Anselmi Palma, Eduardo; Rinchi, Mirko; Howard, Kevin; Talluri, Lorenzo; Fiaschi, Daniele (EDP Sciences, 2023)
This paper describes the current efforts to develop and manufacture a first prototype for a boundary layer pump as a mean to assess future and more complex designs. Following an approach of “learning by doing”, a previous design was re-assessed from a mechanical/workshop point of view. Budget constraints and in-house manufacturing capabilities were taken into consideration to deliver a new design, suitable for quick production. Challenges such as disc holding, gap spacing, pump intake, discharge nozzles, and tolerances were addressed. Structural analysis has been conducted; where every single component has been modelled and sized accordingly to standard practices. As a support of structural analysis, FEM analysis was also performed with the aim of identifying, discussing, and fixing any potentially critical issues, particularly regarding the bolts holding together the discs into the power shaft. Finally, modal analysis was performed in order to test the dynamic response of the rotor: its critical frequencies would be far from the working range of the machine. This paper gives an overview of the critical issues to be taken into account during the mechanical design of boundary layer pump prototypes for different working fluids in the field of power generation and thermal management.